Pengembangan Teknologi Pengolahan Limbah Dan Pakan Fermentasi Untuk Mendukung Program PDB Di Desa Watu Kec. Marioriwawo, Kab. Soppeng, Sulawesi Selatan - Said, Muhammad Irfan; Utamy, Renny Fatmyah; Syawal, Sutomo; Said, Miah (Universitas Mataram, 2024)
There are two aspects of the problems of the cattle farming community in Soppeng Regency, namely the availability of feed and the impact of livestock waste. The largest waste potential in Soppeng Regency, especially Watu Village, is agricultural and livestock waste. However, it has not been utilized optimally. Watu Village, which is rich in organic materials, is one of the reasons for developing this village as an organic farming village in Soppeng Regency. The purpose of this activity is to increase the capacity of knowledge and skills of partner farmers in processing organic waste from livestock and agriculture to be produced into compost fertilizer or fermented feed (silage). A total of 3 community group partners were involved, namely: 1) the